Chromosome contribution to Andean Polyploid Species of Senecio (Asteraceae), from Argentina - López, Mariana C. (2002)
Meiotic chromosome numbers were determined and observations of meiotic behavior were made in six species and two hybrid specimens of Senecio L. (Asteraceae). Two different numbers were found: 2n=4x=40 in S. pogonias Cabr., S. ragonesei Cabr., S. sectilis Griseb. and S. viridis Phil. var. radiatus R. E. Fr. and 2n=8x=80 in S. subulatus D. Don. var. subulatus and in S. uspallatensis Hook. et Arn.; the latter showed the same chromosome number previously reported. The chromosome number of the hybrid individuals was 2n=4x=40, being their putative parents S. ragonesei and S. sectilis. B chromosomes were found in some individuals of S. pogonias, S. sectilis, S. subulatus var. subulatus and S. uspallatensis. Many meiotic irregularities such as bridges, fragments, laggard chromosomes, micronuclei and cellular fusion were observed. The results are analyzed in relation to the persistence and success of these polyploids, and the speciation mechanisms operating within this group are discussed.